"I Hope I Get Movie‐star Teeth": Doing the Exceptional Normal in Orthodontic Practice for Young People. (2nd February 2016) - Wickström, Anette
Abstract : Orthodontics offer young people the chance to improve their bite and adjust their appearances. The most common reasons for orthodontic treatment concern general dentists', parents' or children's dissatisfaction with the esthetics of the bite. My aim is to analyze how esthetic norms are used during three activities preceding possible treatment with fixed appliances. The evaluation indexes signal definitiveness and are the essential grounds for decision‐making. In parallel, practitioners and patients refer to self‐perceived satisfaction with appearances. Visualizations of divergences and the improved future bite become part of an interactive process that upholds what I conceptualize as "the exceptional normal." Insights into this process contribute to a better understanding of how medical practices intended to measure and safeguard children's and young people's health at the same time mobilize patients to look and feel better. The article is based on an ethnographic study at two orthodontic clinics.